STRATEGI PERSAINGAN USAHA ANGKUTAN BARANG PT. KERETA LOGISTIK - PAHRUDIN, CECEP; WIBOWO, FAJAR PRASTIYO (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
Train is an effective vehicle to transport large cargo in a long distance trip though it still needs other transport (multimode transport) to load and unload the cargo. PT. KALOG (Kereta Logistik) is a new comer in the industry but considered to be a good and viably counted in the cargo transport industry. Based on the company information, this achievement could be reached due to its qualified human resources though it does not have, yet, occupied equipment and facilities. This study is aimed at finding out the strategies of the company in gaining the popularity among other logistic transport companies. This study is using qualitative and SWOT analysis. Based on the result, PT. KALOG is in the first quadrant which shows that the best strategy to be applied is Growth Oriented Strategy or Strategi SO.